Le Processus de Composition dans la Musique Instrumentale du Québec - Joyal, Jean-Pierre (MUSICultures, 1980)
In discussing the development of Quebecs instrumental music Jean-Pierre Joyal notes that while French-Canadian songs come mainly from France, much of the dance music is inspired by the music of the British Isles. However, in Quebec the melodies are influenced by the regional styles of the fiddlers and accordionists. He illustrates by looking at variations of the “Democratic Rage Hornpipe” as played by five different Quebec musicians.